Thermal aspects in friction stir process of AISI 316L: Numerical and experimental investigation. Issue 1 (6th January 2020) - Chamoret, D.; Lebaal, N.; Roman, A.; Schlegel, D.; Langlade, C.
ABSTRACT: Friction stir processing (FSP) is an innovative surface engineering method, considered as a green processing technique. A good physical understanding of the process can be reached by the combined efforts of experimental examination and numerical modeling. In this paper, numerical and experimental investigations of heat generation during FSP of AISI 316L were performed. A 3D nonlinear thermal model was developed to simulate the thermal history. The simulated temperature distributions were compared with experimental values.